Gene Expression Profiles for Macrophage in Tissues in Response to Different Exercise Training Protocols in Senescence Mice - Uchida, Masataka; Horii, Naoki; Hasegawa, Natsuki; Fujie, Shumpei; Oyanagi, Eri; Yano, Hiromi; Iemitsu, Motoyuki (Frontiers in Sports and Active Living, 2019)
Age-induced chronic inflammation is prevented by aerobic and resistance exercise training. However, the mechanism of exercise effects on chronic inflammation in each tissue remains unclear. The aim of this study was to investigate the effects of resistance and aerobic training on gene expression profiles for macrophage infiltration and polarization (M1/M2 ratio) with chronic inflammation in various tissues of aged mice. Male 38-week-old SAMP1 mice were randomly divided into three groups, namely, sedentary-control (Aged-Con), aerobic training (Aged-AT; voluntary running), and resistance training for 12-weeks (Aged-RT; climbing ladder). Resistance and aerobic exercise training prevented an increase in circulating TNF- levels in aged mice, concomitant with decreases in tissue inflammatory cytokine (TNF- and IL-1) mRNA expression in the heart, liver, small intestine, brain, aorta, adipose, and skeletal muscle, but did not change the levels in the lung, spleen, and large intestine. Moreover, resistance and aerobic exercise training attenuated increases in F4/80 mRNA expression (macrophage infiltration), ratio of CD11c/CD163 mRNA expression (M1/M2 macrophage polarization) and MCP-1 mRNA expression (chemokine: a regulator of chronic inflammation) in the chronic inflamed tissues of aged mice. These results suggest that resistance and aerobic exercise training-induced changes in gene expression for macrophage infiltration and polarization in various tissues might be involved in prevention of age-related chronic inflammation.